Rich and responsible: Is ESG a luxury good? - Steffen Andersen; Dmitry Chebotarev; Fatima Zahra Filali-Adib; Kasper M. Nielsen (Danmarks Nationalbank, 2024)
We study whether investors perceive responsible investments (i.e., investments in assets with environmental or social benefits) as luxury goods. We exploit windfall wealth due to inheritance from parental death to obtain plausibly exogenous variations in wealth. We show that windfall wealth increases the likelihood of holding responsible mutual funds and green stocks. Our findings indicate that both supply factors (e.g., bank advice) and demand factors (e.g., preferences) play a role in shaping allocations to responsible investments. Notably, beneficiaries with a history of charitable donations exhibit a stronger response, emphasising the influence of a "warm glow" effect on portfolio compilation.
Keywords: 330; Investments